Compensation Surveys: The Good, the Bad and the Ugly. (March 2014) - Canavan, Judy
This article examines the current state of compensation surveys, including a review of the broad range of compensation surveys available ranging from large published surveys to magazine surveys and repackaged survey data. The issues surrounding participation, quality and the applicability of the data are discussed. The article also suggests actions that compensation stakeholders can take to improve the integrity of external market pay data as a reliable tool.